Progress in sub-femtosecond control of electron localization in molecules - Singh, K.P. (Indian Academy of Sciences, 2014)
Recent advances in controlled generation of intense, ultrashort laser pulses in the femtosecond and attosecond time-scales have pushed new avenues of research in the coherent control of ultrafast electron dynamics in atoms and molecules. We present a topical review on the phenomenon of control of electron localization in small dissociating molecules. By creating and controlling coherent superposition of the symmetric and antisymmetric electronic states, it becomes possible to confine the evolving electron cloud onto a preferred nucleus, thereby steering the molecule towards a desired dissociation route. We discuss the origin of the idea and various mechanisms to achieve electron localization in small molecules. To highlight recent experimental progress, we explain how one can employ few-cycle IR pulses and different attosecond extreme ultraviolet (EUV) pulses in various ways to successfully demonstrate the control of electronic dynamics. Future research opportunities and challenges on this topic are envisioned.
Keywords: Attosecond physics; Intense field; Coherent control